Thrombotic Microangiopathy Caused by Gemcitabine in a Patient with Duodenal Cancer - Jeyachandran Dhanapriya; Sankarakumar GaneshAravind; Thanigachalam Dineshkumar; Ramanathan Sakthirajan; Balasubramaniyan T; Natarajan Gopalakrishnan (Archives of Clinical Nephrology - Peertechz Publications, 2017)
Gemcitabine (2',2'-difl uorodeoxycytidine) is a potent pyrimidine antimetabolite and was introduced in 1987. It is commonly used for various tumors including non-small cell lung cancer, pancreatic cancer, breast cancer, ovarian can cer and renal cell carcinoma at advanced stages. Thrombotic microangiopathy (TMA) is characterized by microangiopathic hemolytic anemia (MAHA), thrombocytopenia and acute kidney injury. We report here a 45-year-old male patient with duodenal cancer, who developed acute onset breathlessness, oliguria, accelerated hypertension and acute kidney injury (AKI) after having received chemotherapy with gemcitabine for six months. Renal biopsy showed features of TMA. He was treated with plasmapheresis and his renal function recovered near normal. New-onset/exacerbated hypertension, declining renal function, pulmonary/cardiac symptoms and neurological signs in patients with gemcitabine therapy should consider as warning signs of impending TMA. The primary goal of management is discontinuation of drug and prognosis is generally unfavorable. Hence a high degree of suspicion is needed for early diagnosis of gemcitabine induced TMA.